Dynamic regulation of Rgs16 and its correlation with Neuregulin1 expression in acute and chronic nerve injury - García-Bejarano, Marina; Aucello, Riccardo; Zen, Federica; El Soury, Marwa; Cordero, Francesca; de la Fuente, Jesús M.; Perroteau, Isabelle; Ronchi, Giulia; Gambarotta, Giovanna (Frontiers in Cell and Developmental Biology, 2025)
Introduction: Regulators of G Protein Signaling (RGS) form a gene family that modulates G protein-coupled receptor signaling by enhancing the GTPase activity of the Gα-GTP complex, effectively inhibiting G protein-dependent signal transduction cascades. While RGSs are expressed across many organs, including the central nervous system, few data are available for the peripheral nervous system (PNS).Methods and Results: To investigate potential links between RGS and PNS, open-access single-cell RNA sequencing datasets were analyzed, focusing on mice intact sciatic nerves and distal stumps at 3 and 9 days post-transection. Rgs16 emerged as the RGS member most highly expressed by Schwann cells after injury, suggesting its involvement in nerve degeneration. To further explore Rgs16 behavior in nerve injury, its expression was assessed at mRNA level at different time points in the median nerve of adult rats under regenerating conditions following mild (crush) or more severe (end-to-end repair) traumatic injury, and under degenerating conditions. Results revealed that Rgs16 expression increased 3 days after injury, declining under regenerating conditions, but remaining high in degenerating conditions. To examine the role of Rgs16 in chronic nerve degeneration, its expression was evaluated in a pathological model of Charcot-Marie-Tooth disease type-1A (CMT1A), a chronic demyelinating peripheral neuropathy. Analysis of publicly available RNA sequencing data from sciatic nerves of wild-type and CMT1A rats during development showed a significant upregulation of Rgs16 in transgenic rats at P18. Interestingly, this upregulation mirrored the expression pattern of Neuregulin1 (Nrg1), a gene critical for Schwann cell dedifferentiation and demyelination, strongly upregulated in traumatic and chronic nerve injuries. To explore a potential NRG1-RGS16 link, primary Schwann cell cultures were treated with recombinant NRG1β1, which induced an increase in Rgs16 expression.Discussion: These findings suggest a potential feedback mechanism where transient Rgs16 upregulation in response to injury and/or NRG1 might negatively regulate NRG1 release through RGS16-mediated inhibition of GPCR/ErbB transactivation. This study highlights the dynamic role of Rgs16 in traumatic and chronic nerve injuries, implicating its involvement in processes of nerve degeneration, regeneration, and possibly neuropathic pain. Further investigations are needed to clarify RGS16 function, which could pave the way for novel therapeutic strategies to enhance nerve regeneration and alleviate neuropathic pain.